A MINERALOGY AND CHLORITE CHEMISTRY CONSTRAINTS ON THE FORMATION CONDITION OF PROPYLITIC ALTERATION IN THE TUJUH BUKIT PORPHYRY DEPOSIT, EAST JAVA, INDONESIA - Por, Vannak; Idrus, Arifudin; Setiawan, Nugroho Imam; Takahashi, Ryohei; Takahashi, Ran; Abrar, Miftahul (INTAN Jurnal Penelitian Tambang, 2025)
Propylitic alteration develops chlorite, epidote, and calcite assemblages commonly found in porphyry copper–gold deposits. This study aims to understand the formation temperature, oxygen, and sulfur fugacity of chlorite, a characteristic central element of propylitic-related minerals such as epidote and calcite, using a combination of qualitative and quantitative experimental methods. The propylitic alteration forming condition was analyzed in detail using a superprobe (JXA-iSP100) and Electron Probe Micro Analysis (EPMA) at a voltage of 15.0 kV. The chlorite composition is relatively homogeneous, and displayed as Mg-rich chlorite (Type-I) within AlIV-Mg-Fe, ripidolite with respect to Si vs Fe/(Fe+Mg). The chlorite geothermometer indicates that the crystallizing temperature ranges from 288.30 to 332.82°C. The oxygen and sulfur fugacity log fO2 and log fS2 of chlorite are low ranges (– 70.4 to – 51.85) and (– 32.55 to – 20.65), respectively. The analyses identify the mineral as true epidote, with spatial variations indicating Fe occurs as Fe³⁺ and Mn as Mn²⁺. However, the examined proportion of moles of the significant elements (Mg, Ca, Fe, Mn) indicates that calcite is present in hydrothermal systems.